Strategi Pencegahan Perilaku Ciberbullying Melalui Pelatihan Keterampilan Sosial Bagi Guru Bimbingan Dan Konseling Di Kabupaten Pangkep - hasbahuddin, hasbahuddin; Rahmatia, Rahmatia; Alam, Aztri Fithrayani (STKIP Andi Matappa, 2020)
The problems in this program are about cyberbullying behavior in schools that immediately needs treatment, counseling guidance teachers lack sufficient references to prevent cyberbullying behavior in schools, counseling guidance teachers do not understand the cyberbullying behavior prevention model, teachers need practical models or guidelines for preventing cyberbullying behavior schools, teachers have not practically understood the use of social skills to prevent cyberbullying behavior in schools. The solution given is in the form of training on social skills for counseling teachers who are members of MGBK SMP in Pangkep Regency. In this activity, counseling guidance teachers are given training on social skills. This activity is carried out in a training setting where the teachers are trained on the skills students must have in order to avoid the behavior. Training teachers to master social skills techniques to prevent cyberbullying behavior in schools, the material is, a) self management, b) peer relations, and c) assertion. Finally, participants were given the task of applying the results of the training to students at school which was then carried out by a mentoring process by conducting regular FGDs. The results of this activity are in the form of an increase in partners' knowledge and understanding of social skills to prevent cyberbullying behavior in schools. besides that partners can also implement program results in their respective schools.